Beam-splitting code for light scattering by ice crystal particles within geometric-optics approximation. (October 2015) - Konoshonkin, Alexander V.; Kustova, Natalia V.; Borovoi, Anatoli G.
Abstract: The open-source beam-splitting code is described which implements the geometric-optics approximation to light scattering by convex faceted particles. This code is written in C++ as a library which can be easy applied to a particular light scattering problem. The code uses only standard components, that makes it to be a cross-platform solution and provides its compatibility to popular Integrated Development Environments (IDE׳s). The included example of solving the light scattering by a randomly oriented ice crystal is written using Qt 5.1, consequently it is a cross-platform solution, too. Both physical and computational aspects of the beam-splitting algorithm are discussed. Computational speed of the beam-splitting code is obviously higher compared to the conventional ray-tracing codes. A comparison of the phase matrix as computed by our code with the ray-tracing code by A. Macke shows excellent agreement. Highlights: The beam-splitting code is presented as open-source software. Both physical and computational aspects of the code are discussed. Computational speed of the code is higher than ray-tracing codes. A comparison with the ray-tracing Macke׳s code shows excellent agreement.